Novel role of HIV-1 Nef in regulating the ubiquitination of cellular proteins - Ghaly, Maria; Proulx, Jessica; Borgmann, Kathleen; Park, In-Woo (Frontiers in Cellular and Infection Microbiology, 2023)
Our recent data established that HIV-1 Nef is pivotal in determining the fate of cellular proteins by modulating ubiquitination. However, it is unknown which proteins are ubiquitinated in the presence of Nef, a question critical for understanding the proliferation/restriction strategies of HIV-1 in infected cells. To identify cellular proteins ubiquitinated by Nef, we conducted a proteomic analysis of cellular proteins in the presence and absence of Nef. Proteomic analysis in HEK293T cells indicated that 93 proteins were upregulated and 232 were downregulated in their ubiquitination status by Nef. Computational analysis classified these proteins based on molecular function, biological process, subcellular localization, and biological pathway. Of those proteins, we found a majority of molecular functions to be involved in binding and catalytic activity. With respect to biological processes, a significant portion of the proteins identified were related to cellular and metabolic processes. Subcellular localization analysis showed the bulk of proteins to be localized to the cytosol and cytosolic compartments, which is consistent with the known function and location of Nef during HIV-1 infection. As for biological pathways, the wide range of affected proteins was denoted by the multiple modes to fulfill function, as distinguished from a strictly singular means, which was not detected. Among these ubiquitinated proteins, six were found to directly interact with Nef, wherein two were upregulated and four downregulated. We also identified 14 proteins involved in protein stability through directly participating in the Ubiquitin Proteasome System (UPS)-mediated proteasomal degradation pathway. Of those proteins, we found six upregulated and eight downregulated. Taken together, these analyses indicate that HIV-1 Nef is integral to regulating the stability of various cellular proteins via modulating ubiquitination. The molecular mechanisms directing Nef-triggered regulation of cellular protein ubiquitination are currently under investigation.